2019
DOI: 10.31992/0869-3617-2018-27-12-126-135
|View full text |Cite
|
Sign up to set email alerts
|

Talents – to Business: Support for Entrepreneurial Strategies of Student Youth

Abstract: The article assesses the changes in the role of classical universities in transforming the socio-economic environment in territories where they are located, addresses the problems of developing effective talent management systems and innovation and research infrastructure of business type. In the face of a new technological paradigm requirements for training future specialists change, they include not only transferring basic and professional knowledge, but development of students’ creative abilities, activatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results determined the level of importance for employers and the level of their satisfaction with the theoretical, practical and socio-psychological training of university graduates. It was found that the interaction between organizations and universities on providing joint training is important to improve the quality of graduates training and eliminate the mismatch in the labor market [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The results determined the level of importance for employers and the level of their satisfaction with the theoretical, practical and socio-psychological training of university graduates. It was found that the interaction between organizations and universities on providing joint training is important to improve the quality of graduates training and eliminate the mismatch in the labor market [23,24].…”
Section: Discussionmentioning
confidence: 99%